A Bibliometric Analysis of Global Research From 1928 To 2019 On Mobilization with Movement on Functional Disability in Low Back Pain - Chitale, Neha; Lalwani, Lajwanti (The Scientific Temper, 2025)
Functional disability is the inability to perform day to day activity. Functional disability can be present because of various reasons. For the elderly population about the age of 65 the prevalence of functional disability was found to be 34.6% for activities of daily living, and 53.5% for instrumental activities of daily living. Functional disability hampers social as well as personal lifestyle. Literature published from 1928 to 2019 was obtained from PubMed advanced database. Keywords used in the data collection were functional disability, movement with mobilization, and low back pain, and NPRS SAS software was used to analyze the relationship between publication and country, journals, authors, and keywords Bibliometric analysis of functional disability and mobilization with movement from 1928 to 2019 showed a total of 7138 articles, with a rate of 12 documents per year. Bibliometric analysis was done from the data collected from the PubMed advanced server. The data collected have the most used keywords and the number of documents published in a year. The country that contributed the maximum to the studies was also seen in the bibliometric analysis.